2020
DOI: 10.1111/all.14314
|View full text |Cite
|
Sign up to set email alerts
|

A novel whole blood gene expression signature for asthma, dermatitis, and rhinitis multimorbidity in children and adolescents

Abstract: Background: Allergic diseases often occur in combination (multimorbidity). Human blood transcriptome studies have not addressed multimorbidity. Large-scale gene expression data were combined to retrieve biomarkers and signaling pathways to disentangle allergic multimorbidity phenotypes. Methods: Integrated transcriptomic analysis was conducted in 1233 participants with a discovery phase using gene expression data (Human Transcriptome Array 2.0) from whole blood of 786 children from three European birth cohorts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 34 publications
5
59
0
3
Order By: Relevance
“…Indeed, data from genome-wide association studies (GWAS) have demonstrated that allergic diseases and traits share a large number of genetic susceptibility loci, of which IL33, IL1RL1 (also known as IL33R), IL13-RAD50, C11orf30 (also known as EMSY)-LRRC32 and TSLP seem to be important for multimorbid allergic diseases 18,23 . In addition, rhinitis was associated with TLR expression, whereas AR associated with asthma was associated with IL5 and IL33, suggesting a different genetic cause for AR alone compared with multimorbid AR 24 . Further research is warranted to explore transcriptomic signatures as biomarkers for single and multimorbid allergic diseases.…”
Section: Risk Factorsmentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed, data from genome-wide association studies (GWAS) have demonstrated that allergic diseases and traits share a large number of genetic susceptibility loci, of which IL33, IL1RL1 (also known as IL33R), IL13-RAD50, C11orf30 (also known as EMSY)-LRRC32 and TSLP seem to be important for multimorbid allergic diseases 18,23 . In addition, rhinitis was associated with TLR expression, whereas AR associated with asthma was associated with IL5 and IL33, suggesting a different genetic cause for AR alone compared with multimorbid AR 24 . Further research is warranted to explore transcriptomic signatures as biomarkers for single and multimorbid allergic diseases.…”
Section: Risk Factorsmentioning
confidence: 98%
“…In addition, there are probably common genes associated with asthma and AR and specific genes associated with AR alone. Combining big data analyses (such as from the MASK-air application 135 ), classical epidemiological studies, in silico analysis, transcriptomics using microarray data (as exemplified in MeDALL 22,24,35 ) or RNA sequencing 176 has led to the reclassification of the mechanisms of allergic diseases. For example, polysensitization and multimorbidity represent the extreme allergic phenotype, starting early in life, and are associated with IL5 and IL33 activation.…”
Section: Mechanisms and Multimorbiditymentioning
confidence: 99%
“…AD displays a highly complex pathophysiology and heterogeneous phenotypes, which are illustrated by different features such as age of disease onset, variable response to triggers, spectrum of severity, barrier defect, potential of IgE autoreactivity and comorbidities (asthma, rhinitis, food allergy and infections) (1,2,3,4,5,6). Similar to asthma, AD research is developing and shaping precision medicine approaches aiming towards a biomarker based molecular taxonomy (7,8,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of interest to examine the association between the GWAS risk loci of asthma and AR. IL-33 has been highlighted as an important initiating factor for allergic asthma, and a recent study on whole blood gene expression profiles has revealed a consistent overexpression of the IL1RL1 gene, which encodes IL-33 receptor ST2, in patients diagnosed with multiple morbidities for asthma, dermatitis and rhinitis compared with normal controls (68). Therefore, the present study aimed to explore whether polymorphisms in IL-33 also affect the susceptibility to AR.…”
Section: Discussionmentioning
confidence: 93%